2014
DOI: 10.1038/onc.2014.219
|View full text |Cite
|
Sign up to set email alerts
|

PHF2 histone demethylase acts as a tumor suppressor in association with p53 in cancer

Abstract: Plant homeodomain finger 2 (PHF2) has a role in epigenetic regulation of gene expression by demethylating H3K9-Me2. Several genome-wide studies have demonstrated that the chromosomal region including the PHF2 gene is often deleted in some cancers including colorectal cancer, and this finding encouraged us to investigate the tumor suppressive role of PHF2. As p53 is a critical tumor suppressor in colon cancer, we tested the possibility that PHF2 is an epigenetic regulator of p53. PHF2 was associated with p53, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
72
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(77 citation statements)
references
References 34 publications
(44 reference statements)
2
72
0
Order By: Relevance
“…For example, MORC ATPases have been shown to be involved in heterochromatin silencing in eukaryotes [66] and following DNA damage, MORC2 can facilitate chromatin remodeling and promote gamma-H2AX induction [67]. As another example, PHF2 is a tumor suppressor that is required for the anticancer effects of doxorubicin in cell lines with active p53 [68]. Finally, CBX8 is part of the polycomb repressive complex 1 (PRC1) [69] involved in the transition from a polycomb-repressed to active chromatin state during ES cell differentiation [70].…”
Section: Discussionmentioning
confidence: 99%
“…For example, MORC ATPases have been shown to be involved in heterochromatin silencing in eukaryotes [66] and following DNA damage, MORC2 can facilitate chromatin remodeling and promote gamma-H2AX induction [67]. As another example, PHF2 is a tumor suppressor that is required for the anticancer effects of doxorubicin in cell lines with active p53 [68]. Finally, CBX8 is part of the polycomb repressive complex 1 (PRC1) [69] involved in the transition from a polycomb-repressed to active chromatin state during ES cell differentiation [70].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that PHF2 can modulate p53 by demethylating H3K9me2, and down-regulation of PHF2 expression occurs in colon and stomach cancer [16]. In the study, they suggested that PHF2 acts as a tumor suppressor by regulating the function of p53 [16].…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, only a few studies have investigated the association of PHF2 expression with human cancers, such as breast cancer, esophageal cancer and squamous cell carcinoma of the head and neck [13-15]. A recent study has shown that PHF2 can act as a tumor suppressor through epigenetic regulation of p53 and shows reduced expression in colon cancer and stomach cancer tissues [16]. However, there has been no report of PHF2 expression in CCRCC.…”
mentioning
confidence: 99%
“…PHF8 is required for normal development and mutations in the gene cause X-linked mental retardation, but elevated expression of PHF8 has also been shown to be oncogenic in solid cancer [15,16]. PHF2, on the contrary, has been described as a potential tumor suppressor [17,18]. …”
Section: Kdm2/phfmentioning
confidence: 99%